Quantitative EEG assessment. - Thakor, N.V.
The authors present quantitative results to support the idea that hypothermia-related changes in the brain's electrical activity can be objectively tracked in real time by quantitative EEG (qEEG). This presents the potential for qEEG as a real-time monitoring technique to evaluate hypothermia therapy for brain injury. The potential ability of qEEG to provide an objective estimation of injury and recovery is also presented. This may be used to stratify the degree of injury sustained by the brain. The use of IQ in the preliminary work presented here showed that the qEEG measure indicates that EEG data under hypothermia contained more information than those under normothermia. In the longer term, the authors hope that the qEEG tool may be useful in the intensive care setting as a simple and easy-to-interpret measure that will enhance bedside care.
Keywords: Bedside care; Brain electrical activity; Brain injury; Hyperthermia-related changes; Intensive care setting; Quantitative EEG assessment; Real-time monitoring technique